2020
DOI: 10.1002/jsfa.10946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benzothiadiazole treatment on quality and anthocyanin biosynthesis in plum fruit during storage at ambient temperature

Abstract: BACKGROUND: Plums tend to experience a reduction in fruit quality due to ripening and they deteriorate quickly during storage at room temperature. Benzothiadiazole (BTH) is a plant elicitor capable of inducing disease resistance in many crops. In this study, the effect of BTH treatment on fruit ripening, fruit quality, and anthocyanin biosynthesis in 'Taoxingli' plum was investigated. RESULTS:The results showed that BTH treatment could accelerate fruit ripening without affecting the incidence of fruit decay or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The relative expressions of four genes relevant to endogenous MLT synthesis were assayed using real‐time quantitative PCR based on Huan et al (2020) previous method. Primer Premier 5 software was used to design primers (Table 1) for the tested genes.…”
Section: Methodsmentioning
confidence: 99%
“…The relative expressions of four genes relevant to endogenous MLT synthesis were assayed using real‐time quantitative PCR based on Huan et al (2020) previous method. Primer Premier 5 software was used to design primers (Table 1) for the tested genes.…”
Section: Methodsmentioning
confidence: 99%
“…reported that ASM treatment enhanced disease resistance by increasing PAL, C4H and 4CL activities and gene expression, and promoting the content of secondary metabolites. Studies in pitaya, 15 blueberry, 6 strawberry, 37 muskmelon 13 and plum fruit 38 have indicated that postharvest application of ASM could increase anthocyanin and flavonoid content by enhancing PAL, 4CL and C4H activities. ASM treatment also induced disease tolerance in litchi, 10 peach, 18 mango, 31 banana, 32 Yali pear 30 and muskmelon 8 fruit by activating PAL activity as well as phenylalanine and flavonoid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The anthocyanins were extracted from purple potato tubers using a modification of the method described by Huan et al ( 2020 ). One‐gram samples of fresh purple potato tubers were collected in triplicate at each stage (Sa–Sf).…”
Section: Methodsmentioning
confidence: 99%